(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main objective of doing this project is to design and develop a proper converter topology, which better support the energy management and power flow in both direction. In other words to formulate a hybrid energy storage system with battery and supercapacitor (SC), which is able to reduce the stress in the battery. The whole system is designed such that it is applicable in a permanent magnet direct current (PMDC) motor drive for electric vehicle (EV). A proper control strategy has to be developed in order to obtain the optimal solution. There are two topologies (Single unidirectional and bidirectional converter topology, Two bidirectional converter topology) selected to do this work and these two topologies are studied, verified in detail. Also a comparative study of these two topologies is carried out. The entire Simulation of system is done in MATLAB/Simulink.